CFD as a tool for modelling membrane systems - Weihs, G. A. Fimbres; Picazo, Francisco Javier García; Chong, Yie Kai; Lam, Wen Yew; Tan, Jia Xin; Foo, Kathleen; Twong, Weng Fung; Liang, Y. Y. (IWA Publishing, 2024)
Computational fluid dynamics (CFD) is a computer-based numerical method used to analyse systems that involve fluid flow and/or heat and mass transfer (Versteeg & Malalasekera, 2007). CFD bridges the two different approaches for solving engineering problems before the computer era, theoretical and experimental; it relies on mathematical models while being easy to adapt to almost any realistic condition (Anderson & Wendt, 1995). Another feature of CFD is its versatility, as it allows the analysis of systems for a variety of applications such as chemical reactions (Salehi et al., 2016), aerodynamics (Snel, 2003), dispersion of pollutants (Chu et al., 2005), blood flows (Byun & Rhee, 2004), among many others.